2007
DOI: 10.1103/physrevlett.98.138104
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Control of Fixational Eye Movements with Neurophysiological Delays

Abstract: We propose a model for the control of fixational eye movements using time-delayed random walks. Fixational eye movements produce random displacements of the retinal image to prevent perceptual fading. First, we demonstrate that a transition from persistent to antipersistent correlations occurs in data recorded from a visual fixation task. Second, we propose and investigate a delayed random-walk model and get, by comparison of the transition points, an estimate of the neurophysiological delay. Differences betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
81
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(89 citation statements)
references
References 30 publications
7
81
0
1
Order By: Relevance
“…The invariance of the Hurst exponent for different trials for 3 the same participant will be shown. I also validate the proposed method on simulated time series, mimicking the fixational eye movements based on a time-delayed model proposed in [95] and an integrated model introduced in [44]. I speculate that the integrated model describes data more closely, since the obtained results show qualitatively the same behavior.…”
mentioning
confidence: 69%
See 4 more Smart Citations
“…The invariance of the Hurst exponent for different trials for 3 the same participant will be shown. I also validate the proposed method on simulated time series, mimicking the fixational eye movements based on a time-delayed model proposed in [95] and an integrated model introduced in [44]. I speculate that the integrated model describes data more closely, since the obtained results show qualitatively the same behavior.…”
mentioning
confidence: 69%
“…The Hurst exponent, which parameterizes fBm, indicates its correlation behavior and allows the detection of the long-range dependencies inside the signal. Thus, FEM has been investigated so far using the approaches such as DFA and standard deviation analysis (SDA) [8] in work of Mergenthaler and Engbert [95], and a change of the scaling behavior from a persistent behavior on short time scales to anti-persistent behavior on long time scales was observed.…”
Section: Susana Martinez-condementioning
confidence: 99%
See 3 more Smart Citations